Wake Interactions of Two Tandem Semisubmersible Floating Offshore Wind Turbines Based on FAST.Farm - Lei Xue; Jundong Wang; Liye Zhao; Zhiwen Wei; Mingqi Yu; Yu Xue (Journal of Marine Science and Engineering, 2022)
Wake effects commonly exist in offshore wind farms, which will cause a 10–20% reduction of whole power production as well as a 5–15% increase of fatigue loading on the wind turbine main structures. Obviously wake interaction between floating offshore wind turbine (FOWT) is more complicated, and needs careful assessment which is a prerequisite for active wake control (AWC). The primary objective of the present research is to investigate in detail how the wake inflow condition, streamwise spacing, turbulence intensity, and wind shear influence the power performance, platform motion dynamic and structural loading of FOWT. FAST.Farm, developed by the National Renewable Energy Laboratory (NREL), was used for simulating two tandem FOWTs in different conditions. Comparisons were made between FOWTs in different conditions on power performance and platform motion dynamic, which were presented through both time and frequency domain analysis. Damage equivalent loads change in FOWTs interference under typical working conditions were discussed and summarized. Half wake inflow would pose many challenges to the downstream FOWT. These research studies can be incorporated into further offshore wind farm wake models, providing applicable AWC strategies to reduce wake interference effects for higher energy production and for the longer life of FOWT.